PENGARUH PEMBELAJARAN AKUNTANSI DENGAN METODE PEMBELAJARAN KOOPERATIF TIPE TEAM ACCELERATED INSTRUCTION (TAI) TERHADAP PRESTASI BELAJAR DITINJAU DARI AKTIVITAS BELAJAR SISWA KELAS XI SMA N 1 KARTASURA TAHUN AJARAN 2012/2013 - Perwita, Dyah; M.Stats, Siswandari; Ak, Bandi M.Si (Jurnal Pendidikan Insan Mandiri, 2014)
The purposes of this research are to determine: (1) effect of the use Team Accelerated Instruction (TAI) learning type toward accounting learning achievement, (2) effect of student learning activities toward accounting learning achievement, (3) effect interaction Team Accelerated Instruction (TAI) learning type with student learning activities toward accounting learning achievement.This research includes quasi experimental research. The population is class XI student of Kartasura senior secondary school on academic year 2012/2013. The study uses simple random sampling. Data collection techniques are method of documentation, test and questionnaires. Test of hypotheses show: (1) the use of learning methods affect the learning achievement of accounting, (2) students learning activities affect the learning achievement of accounting, (3) interaction learning methods with student learning activities affect the learning achievement of accounting. The multiple comparison test show: (1) TAI method produce learning achievement that is better than lecture method, (2) learning achievements of students who have a high learning activity and medium learning activity is better than the students who have low learning activity, (3) There is no difference in learning achievement of students that uses TAI with high, medium and low learning activities.Keywords: Cooperative type of TAI, Learning Activities, Learning Achievement